Design Space Exploration and Resource Management of Multi/Many-Core Systems - Singh, Amit Kumar; Ganguly, Amlan (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The increasing demand of processing a higher number of applications and related data on computing platforms has resulted in reliance on multi-/many-core chips as they facilitate parallel processing. However, there is a desire for these platforms to be energy-efficient and reliable, and they need to perform secure computations for the interest of the whole community. This book provides perspectives on the aforementioned aspects from leading researchers in terms of state-of-the-art contributions and upcoming trends.